The Effect Of Guided Strategic Planning On Iranian Intermediate English As A Foreign Language (Efl) Learners' Fluency, Accuracy And Lexical Resources In Speaking - Talebi, Seyed Hassan; Moradi, Zahra (Penerbit Universiti Sains Malaysia, 2015)
This study examined the effect of guided strategic planning on the fluency, accuracy and lexical resources in the speaking of Iranian intermediate English as a foreign language (EFL) learners as well as their awareness and use of pre-speaking strategies. For this purpose, 20 first-year students from the University of Mazandaran majoring in English Language and Literature were selected according to the general English proficiency test by Nelson and randomly assigned to experimental and control groups. A picture cued narrative speaking task and a pre-speaking strategies questionnaire were used as pre- and post-tests. The experimental group received 10 sessions of strategic planning coupled with pre-speaking strategy instruction. Analysis of data evidenced that students' overall scores in fluency, accuracy and lexical resources changed from pre-test to post-test. It was also found that speaking accuracy and fluency were most and least affected, respectively. Another finding was that the students' awareness and use of prespeaking strategies increased as a result of the instruction. It is recommended that teachers and material developers couple strategic task planning with pre-speaking strategies so that improvements in speaking are observed.